Prevalence of scrub typhus in pyrexia of unknown origin and assessment of interleukin-8, tumor necrosis factor-alpha, and interferon-gamma levels in scrub typhus-positive patients - Meher Rizvi; Asfia Sultan; Madhav Chowdhry; Mohd Azam; Fatima Khan; Indu Shukla; Haris M Khan (Wolters Kluwer Medknow Publications, 2018)
Background: Scrub typhus is lesser known cause of fever of unknown origin in India. Even if there have been reports documenting the prevalence of scrub typhus in different parts of India, it is still an unknown entity, and clinicians usually do not consider it as differential diagnosis. The present study was performed to document the prevalence of scrub typhus among febrile patients in western part of Uttar Pradesh and to assess the clinical profile of infected patients on the one hand and knowledge, attitude, and practices among clinicians on the other. Materials and Methods: A total of 357 adult patients with fever of more than 5-day duration were recruited. All patients underwent complete physical examination, and detailed clinical history was elicited as per predesigned pro forma. After primary screening to rule out malaria, enteric fever, and leptospirosis infection, secondary screening for scrub typhus was done by rapid screen test and IgM ELISA. Results: Scrub typhus infection was positive in 91 (25.5%) cases. The most common symptoms among the patients were fever (100%), pain in abdomen (79.1%), pedal edema 56 (61.5%), rash 44 (48.3%), headache 44 (48.3%), vomiting 42 (46.1%), constipation 33 (36.2%), cough 28 (30.7%), and lymphadenopathy 20 (21.9%). The median values of interleukin-8, interferon-gamma, and tumor necrosis factor-alpha in healthy controls were 15.54 pg/ml, 7.77 pg/ml, and 54.1 pg/ml, respectively, while the median values of these cytokines in scrub typhus-positive patients were 21.04 pg/ml, 8.74 pg/ml, and 73.8 pg/ml, respectively. Conclusion: Our results highlight that scrub typhus infection is an important cause of pyrexia of unknown origin, and active surveillance is necessary to assess the exact magnitude and distribution of the disease.